2019
DOI: 10.1111/dme.13954
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness as a risk factor for cardiovascular events and all‐cause mortality in people with Type 2 diabetes

Abstract: Aim To quantify the risk of different non‐invasive arterial stiffness measurements with macrovascular disease and all‐cause mortality in high‐risk people with Type 2 diabetes. Methods We conducted a prospective cohort study of 1910 people with Type 2 diabetes included in the Second Manifestations of ARTerial disease (SMART) study. Arterial stiffness was assessed by brachial artery pulse pressure, normal range (≥0.9) ankle–brachial index and carotid artery distension. Cox regression was used to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“…A meta-analysis of longitudinal cohort studies reported a significant association between baPWV and CV mortality [ 22 ]. A few studies have reported that increased arterial stiffness, measured by baPWV or brachial pulse pressure, could predict mortality and CV events in subjects with diabetes [ 17 , 23 ]. Several other prospective studies demonstrated that the optimal cutoff of baPWV for predicting CV mortality in a general population of elderly subjects was 1963 cm/s [ 24 ] and that for predicting a future CV event was 1800 cm/s [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of longitudinal cohort studies reported a significant association between baPWV and CV mortality [ 22 ]. A few studies have reported that increased arterial stiffness, measured by baPWV or brachial pulse pressure, could predict mortality and CV events in subjects with diabetes [ 17 , 23 ]. Several other prospective studies demonstrated that the optimal cutoff of baPWV for predicting CV mortality in a general population of elderly subjects was 1963 cm/s [ 24 ] and that for predicting a future CV event was 1800 cm/s [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the T2D environment, one of the early critical events for CVD complications is the increase in arterial stiffness and endothelial cell damage that contributes to atherosclerosis [ 95 , 96 ]. The high levels of circulating glucose and lipids are significant determinants for both arterial stiffness and carotid intimal media thickness (IMT) [ 97 , 98 ], and this association is only evident in T2D patients [ 99 ].…”
Section: Cardiovascular Disease (Cvd) Complication In T2dmentioning
confidence: 99%
“…There are complex multifactorial links between diabetes and cardiovascular disease [59,60,61,62]. The main pathophysiology cornerstone is a state of chronic, low-level inflammation.…”
Section: Adding Comorbidities: Type-2 Diabetesmentioning
confidence: 99%